Are the Paris’ law parameters dependent on each other? - Marco Paggi; Alberto Carpinteri (Fracture and Structural Integrity)
The question about the existence of a correlation between the parameters C and m of the Paris’ law is re-examined in this paper. According to dimensional analysis and incomplete self-similarityconcepts applied to the linear range of fatigue crack growth, a power-law asymptotic representation relating the parameter C to m and to the governing variables of the fatigue phenomenon is derived. Then, from the observation that the Griffith-Irwin instability must coincide with the Paris’ instability at the onset of rapid crack growth, the exponents entering this correlation are determined. A fair good agreement is found between the proposed correlation and the experimental data concerning Aluminium, Titanium and steel alloys.